Experimental Study on Wire Melting Control Ability of Twin-Body Plasma Arc - Ruiying Zhang; Fan Jiang; Long Xue (Chinese Journal of Mechanical Engineering, 2024)
Abstract The twin-body plasma arc has the decoupling control ability of heat transfer and mass transfer, which is beneficial to shape and property control in wire arc additive manufacturing. In this paper, with the wire feeding speed as a characteristic quantity, the wire melting control ability of twin-body plasma arc was studied by adjusting the current separation ratio (under the condition of a constant total current), the wire current/main current and the position of the wire in the arc axial direction. The results showed that under the premise that the total current remains unchanged (100 A), as the current separation ratio increased, the middle and minimum melting amounts increased approximately synchronously under the effect of anode effect power, the first melting mass range remained constant; the maximum melting amount increased twice as fast as the middle melting amount under the effect of the wire feeding speed, and the second melting mass range was expanded. When the wire current increased, the anode effect power and the plasma arc power were both factors causing the increase in the wire melting amount; however, when the main current increased, the plasma arc power was the only factor causing the increase in the wire melting amount. The average wire melting increment caused by the anode effect power was approximately 2.7 times that caused by the plasma arc power. The minimum melting amount was not affected by the wire-torch distance under any current separation ratio tested. When the current separation ratio increased and reached a threshold, the middle melting amount remained constant with increasing wire-torch distance. When the current separation ratio continued to increase and reached the next threshold, the maximum melting amount remained constant with the increasing wire-torch distance. The effect of the wire-torch distance on the wire melting amount reduced with the increase in the current separation ratio. Through this study, the decoupling mechanism and ability of this innovative arc heat source is more clearly.